Structural reform measures in agriculture - Organisation for Economic Co-operation and Development (OECD) (Paris : Organisation for Economic Co-operation and Development, 1972)
This OECD report was focused on different aspects of agricultural policy particularly, farm sizes, land consolidation, retirement and discontinuation, land transfers and farm enlargements.
lje 06/04/17
Loans
Keywords: Agriculture and state - Congresses; Farms, Size of -Congresses.; Agriculture and state; Agriculture - Economic aspects